ISU KONTEMPORER PERAN NOTARIS DALAM AKAD MURABAHAH DI LEMBAGA KEUANGAN SYARI’AH - Dudi Badruzaman (Muslim Heritage, 2019)
ABSTRACT In the growth and development of the Islamic Financial Institution (LKS) in Indonesia, there are three major challenges: First: how LKS can be an alternative financial institution for the community, especially the Muslim community. Second: Product innovation and growth must develop and still be able to compete with conventional financial institutions. And third: the products offered must still maintain the principles of Islamic shari'a. In providing guarantees of safety and comfort to customers, the role of the notary in the LKS is to provide legality. In the service function, a notary who has an attitude of honesty, fairness, transparency and neutrality (impartial to anyone) becomes an added value for the community to trust sharia financial institutions as a place for murabahah financing contracts that use collateral / collateral as a condition of the financing contract. With the descriptive method, this paper describes how the position and role of the notary in the Murabahah contract in the Syari'ah Financial Institution. In Murabahah financing, the role of the notary as a general official making deed becomes the legal strength of the parties in: making a Deed of Sale (AJB), Fiduciary contract / agreement, Power of Attorney (SKMHT) and Deed of Recognition (APHT) and Recognition Deed Debt. So that the parties who are in agreement can get a guarantee that is legally binding on the contract and can be used as an authentic deed if there is a dispute or something else related to the law. Keywords: Notary Role, Murabahah Agreement, LKS, Authentic Deed.                                                                                                                                                                                       ABSTRAKDalam pertumbuhan dan perkembangan Lembaka Keuangan Syari’ah (LKS) di Indonesia, terdapat tiga tantangan besar:, Pertama: bagaimana LKS bisa menjadi lembaga keuangan alternatif bagi masyarakat, khusunya ummat Islam. Kedua: Inovasi dan pertumbuhan produk harus berkembangan dan tetap bisa bersaing dengan lembaga keuangan konvensional. Dan ketiga: produk-produk yang ditawarkan harus tetap memepertahankan prinsip-prinsip syari’at Islam. Dalam memberikan jaminan keamanan dan kenyamanan pada nasabah, peran notaris di LKS sebagaipemberi  legalitas (kekuatan hukum). Pada fungsi pelayanan, notaris yang memiliki sikap kejujuran, keadilan, transparansi dan netral (tidak memihak siapapun) menjadi nilai tambah untuk masyarakat dapat mempercayai lembaga keuangan syariah sebagai wadah tempat terjadinya akad pembiayaan murabahah yang menggunakan agunan/jaminan sebagai syarat akad pembiayaan tersebut. Dengan metode deskriptif, tulisan ini menguraikan bagaimana kedudukan dan peran notaris dalam akad Murabahah dalam Lembaga Keuangan Syari’ah.  Dalam pembiayaan Murabahah, peran notaris sebagai pejabat umum pembuat akta menjadi kekuatan hukum para pihak dalam: membuat Akta Jual Beli (AJB), akad/perjanjian Fidusia, Surat Kuasa Membebankan Hak Tanggungan (SKMHT) dan Akta Pemberian Hak Tanggungan (APHT) dan Akta Pengakuan Hutang. Sehingga para pihak yang berakad sama-sama mendapatkan jaminan yang berkekuatan hukum atas akadnya dan bisa dipergunakan sebagai akta otentik jika dikemudian hari terdapat sengketa atau hal lain yang berkaitan dengan hukum.Kata kunci: Peran Notaris, Akad Murabahah, LKS, Akta Otentik.